NUMERICAL RESULT FOR VARIATIONAL INEQUALITY PROBLEMS WITH EQUALITY CONSTRAINT - Pham Van Loi (Universitas Gadjah Mada, 2008)
In this paper we present some numerical results for illustrating a theoret- ical results obtained in our investigation in the field of variational inequality problems with constraint in the form of operator equation involving monotone operator.